Restructuring Financial Record System in MSME DN Shop (Motorcycle Accessories Shop) - Nindya Dwi Hutami; Hilda Fachrizah (AIBPM Publisher, 2021)
This thesis research discusses the process of business coaching in MSME motorcycle accessories shops. This study was carried out using a qualitative method and a data collection technique that included an in-depth interview, observation, and documentation. Based on data analysis, MSME has a business target to expand selling motorcycle spare parts. To achieve this target, MSME must improve the financial recording system that can be used for internal decision making and as a reference for investors. The purpose of this research is to improve the financial recording system in MSME. The study's findings include the use of accounting software that has been optimized and customized to provide output financial records that meet the needs of small and medium-sized businesses.